Li2O-Al2O3-SiO2 glass-ceramics
The Li2O-Al2O3-SiO2 system crystallinated glass addresses the issues of cracking and reduced light permeability in semiconductor packaging by optimizing composition to minimize volume shrinkage and enhance light transmission.
Patent Information
- Application Number
- JP2021515875
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-23
- Filing Date
- 2020-03-18
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2040-03-18
AI Technical Summary
Existing crystallinated glasses used for semiconductor chip packaging suffer from high volume shrinkage during crystallization, leading to cracks and reduced light permeability, particularly in the ultraviolet and infrared ranges, due to the use of β-quartz and β-spodumen solid solutions.
A Li2O-Al2O3-SiO2 system crystallinated glass with specific compositional ranges, including 40-90% SiO2, 1-10% Li2O, 5-30% Al2O3, 0-20% SNO2, 0-20% ZRO2, 0-2% Tio2, 0-10% MGO, and 0-10% P2O5, where β-spodumen solid solution is the main crystal, minimizing volume shrinkage and light scattering.
The glass exhibits high permeability across the ultraviolet to infrared range with reduced cracking, maintaining low thermal expansion coefficients, making it suitable for high-density semiconductor packaging.
Smart Images

Figure 0007626979000001 
Figure 0007626979000002 
Figure 0007626979000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a Li2O-Al2O3-SiO2 system crystallized glass. [Background technology]
[0002] In recent years, there has been a demand for smaller and lighter portable electronic devices such as mobile phones, notebook personal computers, and PDAs (Personal Data Assistances). As a result, the mounting space for semiconductor chips used in these electronic devices has become severely limited, making high-density mounting of semiconductor chips an issue. Therefore, high-density mounting of semiconductor packages is being attempted by using three-dimensional mounting technology, i.e., stacking semiconductor chips and connecting each semiconductor chip with wiring.
[0003] As described in Patent Document 1, in a fan-out type wafer level package (WLP), a plurality of semiconductor chips are molded with a resin encapsulant to form a processed substrate, and then, a process of wiring one surface of the processed substrate, a process of forming solder bumps, etc. These processes involve heat treatment at about 200°C, which may cause the encapsulant to deform and the processed substrate to change in size. In order to suppress the dimensional change of the processed substrate, it is effective to use a support substrate for supporting the processed substrate, and in order to effectively suppress the dimensional change of the processed substrate, which has a relatively low expansion, the support substrate may be required to have low expansion characteristics.
[0004] Therefore, the use of Li2O-Al2O3-SiO2-based crystallized glass, which is formed by precipitating Li2O-Al2O3-SiO2-based crystals such as β-quartz solid solution (Li2O·Al2O3·nSiO2 [where 2≦n≦4]) and β-spodumene solid solution (Li2O·Al2O3·nSiO2 [where n≧4]), which are low-expansion crystals, as the main crystals, has been investigated as a supporting substrate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-113341 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, Li2O-Al2O3-SiO2 crystallized glass in which β-quartz solid solution is precipitated as the main crystal has a problem that the volume shrinkage is large when the crystals are precipitated from the mother glass, and it is prone to cracks such as surface peeling and cracks. In addition, Li2O-Al2O3-SiO2 crystallized glass in which β-spodumene solid solution is precipitated as the main crystal has a small volume shrinkage when crystallized and is less likely to crack, but has a problem that it is difficult to transmit laser light (ultraviolet to infrared light) used to fix and separate the processed substrate and the glass substrate due to its low transmittance in the ultraviolet to infrared range.
[0007] An object of the present invention is to provide a Li2O-Al2O3-SiO2 based crystallized glass that has high transmittance in the ultraviolet to infrared range and is resistant to cracking. [Means for solving the problem]
[0008] The Li2O-Al2O3-SiO2 crystallized glass of the present invention contains, in mass%, 40-90% SiO2, 1-10% Li2O, 5-30% Al2O3, 0-20% SnO2, over 20% ZrO2, less than 0-2% TiO2, 0-10% MgO, and 50-10% P2O, and is characterized in that β-spodumene solid solution is precipitated as the main crystal. The Li2O-Al2O3-SiO2 crystallized glass in which β-spodumene solid solution is precipitated has a large crystal grain size of about 500 nm, which is prone to light scattering, and therefore tends to have reduced ultraviolet to infrared light transmittance. However, it has been found that the reduction in light transmittance due to light scattering can be fully compensated for by reducing the TiO2 content to less than 2 mass%. Furthermore, in the Li2O-Al2O3-SiO2-based crystallized glass in which β-spodumene solid solution is precipitated as the main crystal, the amount of volumetric shrinkage when crystals precipitate from the mother glass is small, and cracks are less likely to occur.
[0009] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably further contains, by mass%, 0-10% Na2O, 0-10% K2O, 0-10% CaO, 0-10% SrO, 0-10% BaO, 0-10% ZnO, and 0-10% B2O3.
[0010] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains, by mass %, 0 to 2% of SnO2.
[0011] The Li2O-Al2O3-SiO2 based crystallized glass of the present invention preferably contains, in mass %, 1.5 to 20% ZrO2 and more than 0 to 10% MgO.
[0012] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably further contains, by mass %, 0.10% or less of Fe2O3.
[0013] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of MgO / (Li2O+MgO) of 0.0001 or more, where "MgO / (Li2O+MgO)" is the value obtained by dividing the content of MgO by the total amount of Li2O and MgO.
[0014] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of Al2O3 / (SnO2+ZrO2) of not more than 9. Here, "Al2O3 / (SnO2+ZrO2)" is the value obtained by dividing the content of Al2O3 by the combined amount of SnO2 and ZrO2.
[0015] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of SnO2 / (SnO2+ZrO2+TiO2+P2O5+B2O3) of 0.01 or more. Here, "SnO2 / (SnO2+ZrO2+TiO2+P2O5+B2O3)" is the value obtained by dividing the content of SnO2 by the total amount of SnO2, TiO2, ZrO2, P2O5, and B2O3.
[0016] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of ZrO2 / Li2O of 0.4 or more. Here, "ZrO2 / Li2O" is the value obtained by dividing the content of ZrO2 by the content of Li2O.
[0017] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of (SnO2+ZrO2+TiO2) / (SiO2+Al2O3+Li2O+Na2O+K2O+MgO+CaO+SrO+BaO+ZnO+B2O3+P2O5) of 0.03 or more. Here, "(SnO2+ZrO2+TiO2) / (SiO2+Al2O3+Li2O+Na2O+K2O+MgO+CaO+SrO+BaO+ZnO+B2O3+P2O5)" is the value obtained by dividing the total amount of SnO2, ZrO2, and TiO2 by the total amount of SiO2, Al2O3, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, ZnO, B2O3, and P2O5.
[0018] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of (SiO2+Al2O3) / Li2O of at least 20. Here, "(SiO2+Al2O3) / Li2O" is the value obtained by dividing the total amount of SiO2 and Al2O3 by the content of Li2O.
[0019] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of (Li2O+Na2O+K2O) / ZrO2 of 3.0 or less, where "(Li2O+Na2O+K2O) / ZrO2" is the value obtained by dividing the total amount of Li2O, Na2O, and K2O by the content of ZrO2.
[0020] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of TiO2 / ZrO2 of 0.0001 to 5.0, where "TiO2 / ZrO2" is the value obtained by dividing the TiO2 content by the ZrO2 content.
[0021] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a mass ratio of TiO2 / (TiO2+Fe2O3) of 0.001 to 0.999, where "TiO2 / (TiO2+Fe2O3)" is the value obtained by dividing the TiO2 content by the TiO2 and Fe2O3 contents.
[0022] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains, by mass%, less than 0.05% of HfO2+Ta2O5, where "HfO2+Ta2O5" refers to the total amount of HfO2 and Ta2O5.
[0023] The Li2O-Al2O3-SiO2 based crystallized glass of the present invention preferably contains, by mass %, 7 ppm or less of Pt.
[0024] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains, by mass %, 7 ppm or less of Rh.
[0025] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably contains, by mass %, 9 ppm or less of Pt+Rh, where "Pt+Rh" refers to the total amount of Pt and Rh.
[0026] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / ° C. In this way, the composition can be suitably used in various applications requiring low expansion properties.
[0027] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / °C.
[0028] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / ° C. This allows the composition to be suitably used in various applications requiring low expansion properties over a wide temperature range.
[0029] The Li2O-Al2O3-SiO2 system crystallized glass of the present invention preferably has a colorless appearance.
[0030] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a thickness of 2 mm and a transmittance of 1% or more at a wavelength of 360 nm, making it suitable for use in a variety of applications requiring ultraviolet transmittance.
[0031] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a thickness of 2 mm and a transmittance of 10% or more at a wavelength of 555 nm, which makes it suitable for use in a variety of applications requiring visible light transmittance.
[0032] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a thickness of 2 mm and a transmittance of 35% or more at a wavelength of 1070 nm, which makes it suitable for use in various applications requiring infrared transmittance.
[0033] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thickness of 2 mm, a transmittance of 1% or more at a wavelength of 360 nm, and a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / °C, and is characterized in that β-spodumene solid solution is precipitated as the main crystal. Effect of the Invention
[0034] According to the present invention, it is possible to provide Li2O-Al2O3-SiO2-based crystallized glass that has high transmittance in the ultraviolet to infrared range and is resistant to cracking. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention contains, in mass%, 40-90% SiO2, 1-10% Li2O, 5-30% Al2O3, 0-20% SnO2, more than 20-20% ZrO2, 0-2% TiO2, 0-10% MgO, and 50-10% P2O, and precipitates a β-spodumene solid solution as the main crystal.
[0036] First, the reasons for limiting the glass composition as described above are given below. In the following description of the content of each component, "%" means "mass %" unless otherwise specified.
[0037] SiO2 is a component that forms the skeleton of glass and also constitutes Li2O-Al2O3-SiO2 crystals. The content of SiO2 is preferably 40-90%, 45-85%, 50-85%, 51-84%, 52-83%, 53-82%, 54-81%, 55-80%, 55-78%, 55-75%, 55-73%, 55-72%, 55-71%, 55-70%, 56-70%, 57-70%, 58-70%, 59-70%, 60-70%, 61-69%, 62-68%, 63-67%, and particularly 64-66%. If the content of SiO2 is too low, the thermal expansion coefficient tends to be high, making it difficult to obtain crystallized glass with excellent thermal shock resistance. In addition, chemical durability tends to decrease. On the other hand, if the SiO2 content is too high, the meltability of the glass decreases, the viscosity of the glass melt increases, making it difficult to clarify the glass or mold the glass, which tends to reduce productivity. Also, the time required for crystallization increases, which tends to reduce productivity.
[0038] Li2O is a component that constitutes Li2O-Al2O3-SiO2 crystals, and has a large effect on crystallinity, as well as lowering the viscosity of glass to improve the meltability and formability of glass. The content of Li2O is preferably 1-10%, 2-10%, 2-9%, 2-8%, 2-7%, 2-6%, 2.1-6%, 2.2-6%, 2.3-6%, 2.4-6%, 2.5-6%, 2.5-5%, 2.5-4.9%, 2.5-4.8%, 2.5-4.7%, 2.5-4.6%, 2.5-4.5%, 2.6-4.4%, 2.7-4.3%, 2.8-4.2%, 2.9-4.1%, 3-4%, 3.1-3.9%, and particularly preferably 3.2-3.8%. If the content of Li2O is too low, mullite crystals tend to precipitate and the glass tends to devitrify. In addition, when crystallizing the glass, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, making it difficult to obtain crystallized glass with excellent thermal shock resistance. Furthermore, the meltability of the glass decreases, the viscosity of the glass melt increases, making it difficult to clarify the glass, and making it difficult to mold the glass, which tends to reduce productivity. On the other hand, if the content of Li2O is too high, the crystallinity becomes too strong, making the glass more likely to devitrify, and the crystallized glass more likely to break.
[0039] Al2O3 forms the skeleton of the glass and is a component that constitutes the Li2O-Al2O3-SiO2 crystal. In addition, Al2O3 is a component that coordinates around the crystal nucleus and forms a core-shell structure. The existence of the core-shell structure makes it difficult for crystal nucleus components to be supplied from outside the shell, making it difficult for the crystal nucleus to enlarge, and making it easier for many tiny crystal nuclei to form. The content of Al2O3 is preferably 5-30%, 6-30%, 7-30%, 7-29%, 8-29%, 9-29%, 9-28%, 10-28%, 11-28%, 12-28%, 12-27%, 13-27%, 14-27%, 14-26%, 15-26%, 16-26%, 16.5-26%, 16.5-25.5%, 17-25.5%, 17-25%, 17.5-25%, 18-24.5%, 18-24%, 18.5-24%, 19-24%, 19.5-24%, 19.5-23.5%, 20-23.5%, 20.5-23%, and particularly preferably 21-22.5%. If the content of Al2O3 is too low, the thermal expansion coefficient tends to be high, making it difficult to obtain crystallized glass with excellent thermal shock resistance. Also, chemical durability tends to decrease. Furthermore, the crystal nuclei become large, and the crystallized glass tends to become cloudy. On the other hand, if the content of Al2O3 is too high, the meltability of the glass decreases, the viscosity of the glass melt increases, making it difficult to clarify and mold the glass, and productivity tends to decrease. Also, mullite crystals tend to precipitate, causing the glass to devitrify, and the crystallized glass tends to break.
[0040] SiO2, Al2O3, and Li2O are the main components of the β-spodumene solid solution, which is the main crystal, and the β-quartz solid solution, which is its precursor. Li2O and Al2O3 compensate for each other's charges and dissolve in the SiO2 skeleton. By containing these three components in an appropriate ratio, crystallization proceeds efficiently and low-cost production becomes possible. Therefore, it is preferable that (SiO2+Al2O3) / Li2O is 20 or more, 20.2 or more, 20.4 or more, 20.6 or more, 20.8 or more, and especially 21 or more.
[0041] SnO2 is a component that acts as a clarifier. It is also a nucleation component for precipitating crystals during the crystallization process. On the other hand, if it is contained in a large amount, it is a component that significantly intensifies the coloring of glass. The SnO2 content is 0-20%, 0-18%, 0-16%, 0-14%, 0-12%, 0-10%, 0-8%, 0-8%, 0.01-8%, 0.01-7%, 0.01-6%, 0.01-5%, 0.01-4%, 0.05-4%, 0.05-3.9%, 0.05-3.8%, 0.05-3.7%, 0.05-3.6%, 0.05-3.5%, 0. It is preferable that the content of SnO2 is 0.05-3.4%, 0.05-3.3%, 0.05-3.2%, 0.05-3.1%, 0.05-3%, 0.05-2.9%, 0.05-2.8%, 0.05-2.7%, 0.05-2.6%, 0.05-2.5%, 0.05-2.4%, 0.05-2.3%, 0.05-2.2%, 0.05-2.1%, and particularly 0.05-2%. If the content of SnO2 is too high, the coloring of the crystallized glass becomes strong. In addition, the raw material batch becomes expensive, resulting in high manufacturing costs.
[0042] ZrO2 is a nucleation component for precipitating crystals in the crystallization process. The ZrO2 content is 0 to 20%, 0 to 18%, 0 to 16%, 0 to 14%, 0 to 12%, 0 to 10%, 0 to 9%, 0 to 8%, 0 to 7%, 0 to 6%, 0 to 5.5%, 0 to 5%, 0 to 4.9%, 0.1 to 4.9%, 0.2 to 4.9%, 0.3 to 4.9%, 0.4 to 4.9%, 0.5 to 4.9%, 0.6 to 4.9%, 0.7 to 4.9%, 0.8 to 4.9%, 0.9 to 4.9%, 1 to 4.9%, 1.1 to 4.9%, 1.2 to 4.9%, 1.3 to 4.9%, 1.4 to 1.4%. 4.9%, 1.5 to 4.9%, 1.6 to 4.9%, 1.7 to 4.9%, 1.8 to 4.9%, 1.9 to 4.9%, 2 to 4.9%, 2.1 to 4.9%, 2.2 to 4.9%, 2.3 to 4.9%, 2.4 to 4.9%, 2.5 to 4.9%, 2.6 to 4.9%, 2.7 to 4.9%, 2.8 to 4.9%, 3.0 to 4.8%, 3.1 to 4.7%, 3.2 to 4.6%, 3.3 to 4.5%, 3.4 to 4.4%, 3.5 to 4.3%, and particularly 3.6 to 4.2%. If the content of ZrO2 is too low, crystal nuclei are not sufficiently formed, and coarse crystals are precipitated, which may cause the glass to become cloudy or break. On the other hand, if the ZrO2 content is too high, coarse ZrO2 crystals will precipitate, causing the glass to devitrify and the crystallized glass to break easily. In addition, the raw material batch will be expensive, resulting in high manufacturing costs.
[0043] Since ZrO2 functions as a sparingly soluble nucleating agent and Li2O functions as a flux to promote melting, a small ZrO2 / Li2O ratio allows ZrO2 to be efficiently dissolved. On the other hand, if ZrO2 / Li2O ratio is too small, the low-temperature viscosity drops too much, and the glass becomes more likely to flow during the nucleation process, which involves heat treatment at a relatively low temperature, causing deformation. In addition, if the low-temperature viscosity drops too much, the nucleation rate becomes too fast, making it difficult to control the nucleation process. For this reason, ZrO2 / Li2O is preferably 0.4 or more, 0.42 or more, 0.44 or more, 0.46 or more, 0.48 or more, 0.50 or more, 0.52 or more, 0.53 or more, 0.54 or more, 0.55 or more, 0.56 or more, and particularly 0.57 or more. If ZrO2 / Li2O ratio is too large, the sparingly soluble ZrO2 does not dissolve sufficiently and tends to remain as devitrified particles. Therefore, the upper limit of ZrO2 / Li2O is preferably 4 or less.
[0044] SnO2+ZrO2 is preferably more than 0 to 30%, 0.5 to 25%, 1 to 20%, 1.2 to 17.5%, 1.8 to 15%, 2 to 12.5%, 2.1 to 10%, 2.2 to 10%, 2.3 to 9.5%, 2.4 to 9%, 2.5 to 8.5%, 2.7 to 8%, 2.9 to 7.5%, 3.1 to 7.5%, 3.2 to 7.5%, 3.3 to 7.5%, 3.4 to 7.5%, and particularly 3.5 to 7.5%. If SnO2+ZrO2 is too small, crystal nuclei are difficult to precipitate and crystallization is difficult. On the other hand, if SnO2+ZrO2 is too large, the crystal nuclei become large and the crystallized glass is easily clouded.
[0045] In addition, Al2O3 / (SnO2+ZrO2) is preferably 9 or less, 8.9 or less, 8.8 or less, 8.7 or less, 8.6 or less, 8.5 or less, 8.4 or less, 8.3 or less, 8.2 or less, 8.1 or less, 8 or less, 7.9 or less, 7.8 or less, 7.7 or less, 7.6 or less, 7.5 or less, 7.4 or less, 7.3 or less, 7.2 or less, 7.1 or less, 7 or less, 6.9 or less, 6.8 or less, 6.7 or less, 6.6 or less, 6.5 or less, 6.4 or less, 6.3 or less, 6.2 or less, 6.1 or less, 6 or less, 5.9 or less, 5.8 or less, 5.7 or less, 5.6 or less, and particularly 5.5 or less. If Al2O3 / (SnO2+ZrO2) is too large, the crystal nucleus becomes large, and the crystallized glass is easily clouded.
[0046] TiO2 is a nucleation component for precipitating crystals during the crystallization process. On the other hand, if it is contained in a large amount, it significantly strengthens the coloring of the glass and reduces the translucency. In particular, zirconia titanate crystals containing ZrO2 and TiO2 act as crystal nuclei, but electrons transition from the valence band of the ligand oxygen to the conduction band of the central metal zirconia and titanium (LMCT transition), which contributes to the coloring of the crystallized glass. In addition, if titanium remains in the remaining glass phase, an LMCT transition can occur from the valence band of the SiO2 skeleton to the conduction band of the tetravalent titanium in the remaining glass phase. In addition, a dd transition occurs in the trivalent titanium in the remaining glass phase, which contributes to the coloring of the crystallized glass. Furthermore, when titanium and iron coexist, an ilmenite (FeTiO3)-like coloring appears, and when titanium and tin coexist, the yellow color intensifies and the translucency, especially in the ultraviolet range, tends to decrease significantly. Therefore, the TiO2 content is below 0-2%, 0-1.95%, 0-1.9%, 0-1.8%, 0-1.7%, 0-1.6%, 0-1.5%, 0-1.4%, 0-1.3%, 0-1.2%, 0-1.1%, 0-1.05%, 0-1%, 0-0.95%, 0-0.9%, 0-0.85%, 0-0.8%, 0-0.75%, 0-0.7%, 0-0.65%, 0-0.6%, 0-0.55%, 0-0. 5%, 0-0.48%, 0-0.46%, 0-0.44%, 0-0.42%, 0-0.4%, 0-0.38%, 0-0.36%, 0-0.34%, 0-0.32%, 0-0.3%, 0-0.28%, 0-0.26%, 0-0.24%, 0-0.22%, 0-0.2%, 0-0.2%, 0-0.18%, 0-0.16%, 0-0.14%, 0-0.12%, and especially 0-0.1%. However, since TiO2 is easily mixed in as an impurity, if TiO2 is to be completely removed, the raw material batch tends to become expensive and the manufacturing cost tends to increase. In order to suppress an increase in manufacturing costs, the lower limit of the TiO2 content is preferably 0.0003% or more, 0.0005% or more, 0.001% or more, 0.005% or more, 0.01% or more, particularly preferably 0.02% or more.
[0047] TiO2 and ZrO2 are components that can function as crystal nuclei. Ti and Zr are homologous elements, and have similar electronegativity and ionic radius. For this reason, they tend to have similar molecular conformations as oxides, and it has been found that in the coexistence of TiO2 and ZrO2, phase separation is likely to occur in the early stages of crystallization. For this reason, within the range in which coloring is permitted, TiO2 / ZrO2 is preferably 0.0001 to 5.0, 0.0001 to 4.0, 0.0001 to 3.0, 0.0001 to 2.5, 0.0001 to 2.0, 0.0001 to 1.5, 0.0001 to 1.0, and particularly 0.0001 to 0.5. If TiO2 / ZrO2 is too small, the raw material batch tends to become expensive and the manufacturing cost tends to increase. On the other hand, if TiO2 / ZrO2 is too large, the crystal nucleation rate slows down, and the manufacturing cost may increase.
[0048] MgO is a component that dissolves in Li2O-Al2O3-SiO2 crystals and increases the thermal expansion coefficient of Li2O-Al2O3-SiO2 crystals. The content of MgO is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, more than 0-5%, more than 0-4.9%, 0.1-4%, 0.2-3%, 0.3-2%, 0.4-1.5%, 0.5-1%, and particularly 0.6-0.9%. If the content of MgO is too high, crystals containing Mg are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0049] In Li2O-Al2O3-SiO2 crystallized glass, if there is a large difference in the thermal expansion coefficient between the crystal phase after crystallization and the remaining glass phase, there is a risk of surface peeling or cracks from inside the sample. If the solid solubility of Li in the Li2O-Al2O3-SiO2 crystal is too large, the amount of volumetric shrinkage during crystallization becomes large, the thermal expansion coefficient of the crystal phase after crystallization becomes too low, and a large difference in the thermal expansion coefficient between the crystal phase and the remaining glass phase is likely to occur. As a result, surface peeling and cracks such as cracks are likely to occur in the crystallized glass. Therefore, MgO / (Li2O+MgO) is preferably 0.0001 or more, 0.0005 or more, 0.001 or more, 0.005 or more, 0.01 or more, 0.012 or more, 0.014 or more, 0.016 or more, 0.018 or more, 0.02 or more, 0.022 or more, 0.024 or more, 0.026 or more, 0.028 or more, 0.03 or more, 0.032 or more, 0.034 or more, 0.036 or more, 0.038 or more, 0.04 or more, 0.041 or more, 0.042 or more, 0.043 or more, 0.044 or more, 0.045 or more, particularly preferably 0.046 or more, 0.047 or more, 0.048 or more, 0.049 or more, and particularly preferably 0.05 or more. The upper limit of MgO / (Li2O+MgO) is preferably 0.9 or less.
[0050] P2O5 is a component that suppresses the precipitation of coarse crystals and devitrification. It is also a component that may be involved in the ease of phase separation during crystal nucleation. The content of P2O5 is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4.5%, 0-4%, 0-3.9%, 0-3.8%, 0.1-3.5%, 0.2-3.2%, 0.3-2.9%, 0.6-2.6%, 0.9-2.3%, 1.1-2%, 1.2-1.7%, and particularly 1.3-1.5%. If the content of P2O5 is too high, the amount of precipitation of Li2O-Al2O3-SiO2 crystals tends to decrease and the thermal expansion coefficient tends to increase. In addition, if the content of P2O5 is too high, the raw material batch becomes expensive, resulting in high manufacturing costs.
[0051] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention may contain the following components in addition to the above components in the glass composition.
[0052] Na2O is a component that can be dissolved in Li2O-Al2O3-SiO2 crystals, and has a large effect on crystallinity, while lowering the viscosity of glass to improve the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of Na2O is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0.1-4%, 0.2-2%, and particularly 0.3-1%. If the content of Na2O is too high, crystals containing Na are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0053] K2O is a component that can be dissolved in Li2O-Al2O3-SiO2 crystals, and has a large effect on crystallinity, and also reduces the viscosity of glass to improve the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. The content of K2O is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-3%, 0-2%, 0.1-1.5%, 0.2-1%, and particularly 0.3-0.5%. If the content of K2O is too high, crystals containing K are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0054] Li2O, Na2O, and K2O are components that improve the melting and moldability of glass, but if the content of these components is too high, the low-temperature viscosity will drop too much, and the glass may flow too much during crystallization. Li2O, Na2O, and K2O are also components that can deteriorate the weather resistance, water resistance, chemical resistance, etc. of glass before crystallization. If the glass before crystallization is deteriorated by moisture, etc., the desired crystallization behavior and therefore the desired properties may not be obtained. On the other hand, ZrO2 is a component that functions as a nucleating agent, and has the effect of crystallizing preferentially at the beginning of crystallization and suppressing the flow of the remaining glass. In addition, ZrO2 efficiently fills the voids in the glass network, which is mainly composed of SiO2 skeleton, and has the effect of inhibiting the diffusion of protons and various chemical components in the glass network, improving the weather resistance, water resistance, chemical resistance, etc. of glass before crystallization. In order to obtain crystallized glass with the desired shape and properties, (Li2O+Na2O+K2O) / ZrO2 should be appropriately controlled. It is preferable that (Li2O+Na2O+K2O) / ZrO2 is 3.0 or less, 2.8 or less, 2.6 or less, 2.5 or less, 2.48 or less, 2.46 or less, and particularly preferably 2.45 or less.
[0055] CaO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. It is also a component that can be dissolved in Li2O-Al2O3-SiO2 crystals. The CaO content is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1%, and particularly 0-0.5%. If the CaO content is too high, crystals containing Ca are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0056] SrO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. It is also a component that can be dissolved in Li2O-Al2O3-SiO2 crystals. The content of SrO is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1%, and particularly 0-0.5%. If the content of SrO is too high, crystals containing Sr are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0057] BaO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. It is also a component that can be dissolved in Li2O-Al2O3-SiO2 crystals. The content of BaO is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0.3-3%, 0.6-2.5%, 0.9-2%, and particularly 1.1-1.5%. If the content of BaO is too high, crystals containing Ba are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0058] ZnO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. It is also a component for adjusting the thermal expansion coefficient and refractive index of crystallized glass. It is also a component that can be dissolved in Li2O-Al2O3-SiO2 crystals. The content of ZnO is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1%, and particularly 0-0.5%. If the content of ZnO is too high, crystals containing Zn are precipitated, the glass is easily devitrified, and the crystallized glass is easily broken. In addition, the thermal expansion coefficient tends to be too high.
[0059] B2O3 is a component that reduces the viscosity of glass and improves the meltability and moldability of glass. It is also a component that can be involved in the ease of phase separation during crystal nucleation. The content of B2O3 is preferably 0-10%, 0-9%, 0-8%, 0-7%, 0-6%, 0-5%, 0-4%, 0-3%, 0-2%, 0-1%, and particularly 0-0.5%. If the content of B2O3 is too high, the glass is easily devitrified and the crystallized glass is easily broken. In addition, the amount of evaporation of B2O3 during melting increases, which increases the environmental load. Furthermore, if the content of B2O3 is too high, the raw material batch becomes expensive, resulting in high manufacturing costs.
[0060] CaO, SrO, BaO, ZnO, and B2O3 may be mixed in as impurities, and if they are to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress an increase in manufacturing costs when there is no problem with translucency, the lower limits of the contents of CaO, SrO, BaO, ZnO, and B2O3 are preferably 0.0001% or more, 0.0003% or more, and particularly 0.0005% or more, respectively.
[0061] It is known that in Li2O-Al2O3-SiO2 crystallized glass, a phase separation region is formed within the glass before crystal nucleation, and then crystal nuclei composed of ZrO2, TiO2, etc. are formed within the phase separation region. Since SnO2, ZrO2, TiO2, P2O5, and B2O3 are strongly involved in the formation of phase separation, the ratio of SnO2+ZrO2+TiO2+P2O5+B2O3 is preferably 0% or more to 30%, 0.5-25%, 1-20%, 1.2-17.5%, 1.8-15%, 2-12.5%, 2.1-10%, 2.2-10%, 2.3-9.5%, 2.4-9%, 2.5-8.5%, 2.7-8%, 2.9-7.5%, 3.1-7.5%, 3.2-7.5%, 3.3-7.5%, and 3.4-7.5%. SnO2 / (SnO2+ZrO2+TiO2+P2O5+B2O3) is preferably 0.01 or more, 0.015 or more, 0.02 or more, 0.025 or more, 0.03 or more, 0.035 or more, 0.04 or more, 0.045 or more, 0.05 or more, 0.055 or more, 0.06 or more, 0.065 or more, 0.07 or more, 0.085 or more, 0.09 or more, 0.095 or more, 0.1 or more, 0.105 or more, 0.11 or more, 0.115 or more, 0.12 or more, 0.125 or more, and particularly 0.13 or more. If SnO2+ZrO2+TiO2+P2O5+B2O3 is too small, it becomes difficult to form a phase separation region and crystallize. On the other hand, if SnO2+ZrO2+TiO2+P2O5+B2O3 is too much and / or SnO2 / (SnO2+ZrO2+TiO2+P2O5+B2O3) is too small, the phase separation region becomes large and the crystallized glass becomes easily cloudy. The upper limit of SnO2 / (SnO2+ZrO2+TiO2+P2O5+B2O3) is not particularly limited, but is practically 0.9 or less.
[0062] Fe2O3 is a component that enhances the coloring of glass, especially a component that significantly enhances coloring by interacting with TiO2 and SnO2. The content of Fe2O3 is preferably 0.10% or less, 0.08% or less, 0.06% or less, 0.05% or less, 0.04% or less, 0.035% or less, 0.03% or less, 0.02% or less, 0.015% or less, 0.013% or less, 0.012% or less, 0.011% or less, 0.01% or less, 0.009% or less, 0.008% or less, 0.007% or less, 0.006% or less, 0.005% or less, 0.004% or less, 0.003% or less, and especially 0.002% or less. However, since Fe2O3 is easily mixed in as an impurity, if Fe2O3 is to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. In order to suppress an increase in production costs, the lower limit of the Fe2O3 content is preferably 0.0001% or more, 0.0002% or more, 0.0003% or more, 0.0005% or more, and particularly preferably 0.001% or more.
[0063] When titanium and iron coexist, ilmenite (FeTiO3)-like coloring may occur. In particular, in Li2O-Al2O3-SiO2 crystallized glass, titanium and iron components that do not precipitate as crystal nuclei or main crystals after crystallization remain in the remaining glass, and the occurrence of the above coloring may be promoted. In terms of design, it is possible to reduce the amount of these components, but since TiO2 and Fe2O3 are easily mixed in as impurities, if they are to be completely removed, the raw material batch becomes expensive and the manufacturing cost tends to increase. Therefore, in order to suppress the manufacturing cost, TiO2 and Fe2O3 may be contained within the above-mentioned range, and in order to make the manufacturing cost cheaper, both components may be contained within the range in which coloring is allowed. In such a case, TiO2 / (TiO2+Fe2O3) is preferably 0.001 to 0.999, 0.001 to 0.998, 0.001 to 0.997, 0.001 to 0.9996, and particularly preferably 0.001 to 0.995.
[0064] Generally, the β-spodumene solid solution, which is the main crystal of the present invention, and the β-quartz solid solution, which is its precursor, are composed of SiO2, Al2O3, Li2O, etc., but the β-spodumene solid solution has a larger void area in the crystal, and alkali metals and alkaline earth metals are more likely to be dissolved in the solid solution. Therefore, the β-spodumene solid solution is composed of any one or all of SiO2, Al2O3, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, ZnO, B2O3, and P2O5. SnO2, ZrO2, and TiO2 can also be dissolved in the β-spodumene solid solution from the viewpoint of ionic radius, but these components often undergo phase separation at the beginning of crystallization and precipitate as crystal nuclei. Therefore, compared to SiO2, Al2O3, etc., the probability of solid solution is low, and it is highly likely that they exist in a phase (crystal nuclei, residual glass, etc.) different from the main crystal. If the difference in refractive index between the main crystal and other phases is large, it is easy to refract short wavelength light, and there is a risk that the desired translucency cannot be obtained. Therefore, (SnO2+ZrO2+TiO2) / (SiO2+Al2O3+Li2O+Na2O+K2O+MgO+CaO+SrO+BaO+ZnO+B2O3+P2O5) is preferably 0.03 or more, 0.035 or more, 0.04 or more, 0.045 or more, and especially 0.05 or more. If (SnO2+ZrO2+TiO2) / (SiO2+Al2O3+Li2O+Na2O+K2O+MgO+CaO+SrO+BaO+ZnO+B2O3+P2O5) is too large, devitrification particles such as ZrO2 and SnO2 are likely to precipitate. The upper limit of (SnO2+ZrO2+TiO2) / (SiO2+Al2O3+Li2O+Na2O+K2O+MgO+CaO+SrO+BaO+ZnO+B2O3+P2O5) is not particularly limited, but is practically 0.1 or more.
[0065] Pt is a component that can be mixed into glass in the form of ions, colloids, metals, etc., and causes a yellow to brown coloration. This tendency becomes more pronounced after crystallization. Furthermore, after careful investigation, it was found that the inclusion of Pt affects the nucleation and crystallization behavior of the crystallized glass, and may cause the glass to become cloudy. For this reason, it is preferable that the Pt content is 7 ppm or less, 6 ppm or less, 5 ppm or less, 4 ppm or less, 3 ppm or less, 2 ppm or less, 1.6 ppm or less, 1.4 ppm or less, 1.2 ppm or less, 1 ppm or less, 0.9 ppm or less, 0.8 ppm or less, 0.7 ppm or less, 0.6 ppm or less, 0.55 ppm or less, 0.5 ppm or less, 0.45 ppm or less, 0.4 ppm or less, 0.35 ppm or less, and particularly 0.3 ppm or less. Although the inclusion of Pt should be avoided as much as possible, when using general melting equipment, it may be necessary to use Pt components to obtain homogeneous glass. For this reason, if Pt is to be completely removed, the manufacturing cost tends to increase. In the case where coloring is not adversely affected, in order to suppress an increase in manufacturing costs, the lower limit of the Pt content is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.02 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, 0.06 ppm or more, and particularly 0.07 ppm or more. In addition, in the case where coloring is tolerable, Pt may be used as a nucleation agent that promotes the precipitation of main crystals, similar to ZrO2 and TiO2. In that case, Pt may be used as a nucleation agent alone, or may be used as a nucleation agent in combination with other components. In addition, when Pt is used as a nucleation agent, the form is not particularly important (colloid, metal crystal, etc.).
[0066] Rh is a component that can be mixed into glass in the form of ions, colloids, metals, etc., and, like Pt, tends to cause yellow to brown coloring and make crystallized glass opaque. For this reason, the content of Rh is preferably 7 ppm or less, 6 ppm or less, 5 ppm or less, 4 ppm or less, 3 ppm or less, 2 ppm or less, 1.6 ppm or less, 1.4 ppm or less, 1.2 ppm or less, 1 ppm or less, 0.9 ppm or less, 0.8 ppm or less, 0.7 ppm or less, 0.6 ppm or less, 0.55 ppm or less, 0.5 ppm or less, 0.45 ppm or less, 0.4 ppm or less, 0.35 ppm or less, and particularly 0.3 ppm or less. Although the mixing of Rh should be avoided as much as possible, when using general melting equipment, it may be necessary to use Rh components to obtain homogeneous glass. For this reason, if Rh is to be completely removed, the manufacturing cost tends to increase. In the case where coloring is not adversely affected, in order to suppress an increase in manufacturing costs, the lower limit of the Rh content is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.02 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, 0.06 ppm or more, and particularly 0.07 ppm or more. In the case where coloring is tolerable, Rh may be used as a nucleating agent like ZrO2 or TiO2. In that case, Rh may be used as a nucleating agent alone or in combination with other components. In the case where Rh is used as a nucleating agent to promote the precipitation of main crystals, the form is not particularly important (colloid, metal crystal, etc.).
[0067] Furthermore, Pt+Rh is preferably 9 ppm or less, 8 ppm or less, 7 ppm or less, 6 ppm or less, 5 ppm or less, 4.75 ppm or less, 4.5 ppm or less, 4.25 ppm or less, 4 ppm or less, 3.75 ppm or less, 3.5 ppm or less, 3.25 ppm or less, 3 ppm or less, 2.75 ppm or less, 2.5 ppm or less, 2.25 ppm or less, 2 ppm or less, 1.75 ppm or less, 1.5 ppm or less, 1.25 ppm or less, 1 ppm or less, 0.95 ppm or less, 0.9 ppm or less, 0.85 ppm or less, 0.8 ppm or less, 0.75 ppm or less, 0.65 ppm or less, 0.6 ppm or less, 0.55 ppm or less, 0.5 ppm or less, 0.45 ppm or less, 0.4 ppm or less, 0.35 ppm or less, and particularly preferably 0.3 ppm or less. Although the inclusion of Pt and Rh should be avoided as much as possible, when using a general melting facility, it may be necessary to use Pt and Rh components to obtain a homogeneous glass. Therefore, if Pt and Rh are to be completely removed, the manufacturing cost tends to increase. In the case where coloring is tolerable, in order to suppress the increase in manufacturing cost, the lower limit of Pt+Rh is preferably 0.0001 ppm or more, 0.001 ppm or more, 0.005 ppm or more, 0.01 ppm or more, 0.02 ppm or more, 0.03 ppm or more, 0.04 ppm or more, 0.05 ppm or more, 0.06 ppm or more, and particularly 0.07 ppm or more.
[0068] In developing glass materials, it is common to use various crucibles to produce glasses of various compositions. For this reason, platinum and rhodium that have evaporated from the crucible are often present inside the electric furnace used for melting. It has been confirmed that Pt and Rh present inside the electric furnace are mixed into the glass. In order to control the amount of Pt and Rh mixed in, it is possible to control the Pt and Rh content in the glass by selecting the raw materials and crucible materials used, attaching a quartz lid to the crucible, lowering the melting temperature, shortening the melting time, etc.
[0069] As2O3 and Sb2O3 are highly toxic and may pollute the environment during the glass manufacturing process, waste glass processing, etc. For this reason, it is preferable that the Li2O-Al2O3-SiO2-based crystallized glass of the present invention does not substantially contain these components (specifically, less than 0.1 mass %).
[0070] The Li2O-Al2O3-SiO2 crystallized glass of the present invention may contain, in addition to the above components, trace components such as H2, CO2, CO, H2O, He, Ne, Ar, and N2 up to 0.1% each, as long as they do not adversely affect coloring. In addition, if Ag, Au, Pd, Ir, V, Cr, Sc, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th, Pa, U, etc. are intentionally added to the glass, the raw material cost tends to increase and the manufacturing cost tends to increase. On the other hand, when glass containing Ag, Au, etc. is irradiated with light or heat treated, aggregates of these components are formed, and crystallization can be promoted from the starting point. In addition, Pd, etc. have various catalytic effects, and by containing them, it is possible to impart unique functions to glass or crystallized glass. In consideration of these circumstances, when the purpose is to promote crystallization or to impart other functions, the above components may be contained in an amount of 1% or less, 0.5% or less, 0.3% or less, or 0.1% or less, respectively, and if not, the amount is preferably 500 ppm or less, 300 ppm or less, 100 ppm or less, and particularly preferably 10 ppm or less.
[0071] Furthermore, as long as there is no adverse effect on coloration, the Li2O-Al2O3-SiO2-based crystallized glass of the present invention may contain up to 10% in total of SO3, MnO, Cl2, Y2O3, MoO3, La2O3, WO3, HfO2, Ta2O5, Nd2O3, Nb2O5, RfO2, etc. However, since the raw material batches of the above components are expensive and tend to increase the manufacturing cost, they do not have to be added unless there are special circumstances. In particular, since HfO2 has a high raw material cost and Ta2O5 can be a conflict mineral, it is preferable that the total amount of these components be 5% or less, 4% or less, 3% or less, 2% or less, 1% or less, 0.5% or less, 0.4% or less, 0.3% or less, 0.2% or less, 0.1% or less, 0.05% or less, less than 0.05%, 0.049% or less, 0.048% or less, 0.047% or less, 0.046% or less, and especially 0.045% or less.
[0072] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention having the above composition tends to be colorless in appearance.
[0073] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has a thickness of 2 mm and a transmittance at a wavelength of 360 nm of 1% or more, 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 46% or more, 47% or more, 48% or more, 49% or more, and particularly 50% or more. In the case of an application that requires transmission of ultraviolet light, if the transmittance at a wavelength of 360 nm is too low, there is a risk that the desired transmittance cannot be obtained. In particular, when using a YAG laser or the like, it is preferable that the transmittance at a wavelength of 360 nm is high.
[0074] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has a thickness of 2 mm and a transmittance at a wavelength of 555 nm of 10% or more, 15% or more, 20% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, and particularly preferably 70% or more. In the case of an application that requires the transmission of visible light, if the transmittance at a wavelength of 555 nm is too low, the desired transmittance may not be obtained.
[0075] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has a thickness of 2 mm and a transmittance at a wavelength of 1070 nm of 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 79% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, and particularly 85% or more. If the transmittance at a wavelength of 1070 nm is too low, it tends to be green.
[0076] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has a thickness of 2 mm and a transmittance change rate before and after crystallization at a wavelength of 360 nm of 95% or less, 92.5% or less, 90% or less, 87.5% or less, 85% or less, 82.5% or less, 80% or less, 77.5% or less, 75% or less, 72.5% or less, 70% or less, 68.5% or less, and particularly preferably 68% or less. If the transmittance change rate before and after crystallization is reduced, it becomes possible to predict and control the transmittance after crystallization before crystallization, and it becomes easier to obtain the desired transmittance after crystallization. It is preferable that the transmittance change rate before and after crystallization is small not only at a wavelength of 360 nm but also in the entire wavelength range. Here, the "transmittance change rate before and after crystallization" means {(transmittance before crystallization (%)-transmittance after crystallization (%)) / transmittance before crystallization (%)} x 100 (%).
[0077] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention tends to have a low thermal expansion coefficient because a β-spodumene solid solution is precipitated as the main crystal.
[0078] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / ℃, -19×10 -7 / ℃~30×10 -7 / ℃, -18×10 -7 / ℃~30×10 -7 / ℃, -17×10 -7 / ℃~30×10 -7 / ℃, -16×10 -7 / ℃~30×10 -7 / ℃, -15×10 -7 / ℃~30×10 -7 / ℃, -15×10 -7 / ℃~28×10 -7 / ℃, -15×10 -7 / ℃~26×10 -7 / ℃, -14.5×10 -7 / ℃~25×10 -7 / ℃, -13.5×10 -7 / ℃~25×10 -7 / ℃, -12.5×10 -7 / ℃~25×10 -7 / ℃, -11.5×10 -7 / ℃~25×10 -7 / ℃, -10.5×10 -7 / ℃~25×10 -7 / ℃, -10×10 -7 / ℃~24.5×10 -7 / ℃, -10×10 -7 / ℃~23.5×10 -7 / ℃, -10×10 -7 / ℃~22.5×10 -7 / ℃, -10×10 -7 / ℃~21.5×10 -7 / ℃, -10×10 -7 / ℃~20.5×10 -7 / ℃, -9.5×10 -7 / ℃~20×10 -7 / ℃, -9×10-7 / ℃~19.5×10 -7 / ℃, -8.5×10 -7 / ℃~19×10 -7 / ℃, -8×10 -7 / ℃~18.5×10 -7 / ℃, -7.5×10 -7 / ℃~18×10 -7 / ℃, -7×10 -7 / ℃~17.5×10 -7 / ℃, -6.5×10 -7 / ℃~17×10 -7 / ℃, -6×10 -7 / ℃~17×10 -7 / ℃, -6×10 -7 / ℃~16.5×10 -7 / ℃, -6×10 -7 / ℃~16×10 -7 / ℃, -5.5×10 -7 / ℃~16×10 -7 / ℃, -5×10 -7 / ℃~16×10 -7 / ℃, -5×10 -7 / ℃~15.5×10 -7 / ℃, especially -5×10 -7 / ℃~15×10 -7 / ° C. If the thermal expansion coefficient at 20 to 200° C. is too low or too high, the processed substrate is likely to experience large dimensional changes.
[0079] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / ℃, -19×10 -7 / ℃~30×10 -7 / ℃, -18×10 -7 / ℃~30×10 -7 / ℃, -17×10 -7 / ℃~30×10 -7 / ℃, -16×10 -7 / ℃~30×10 -7 / ℃, -15×10 -7 / ℃~30×10 -7 / ℃, -15×10 -7 / ℃~28×10 -7 / ℃、-15×10 -7 / ℃~26×10 -7 / ℃、-14.5×10 -7 / ℃~25×10 -7 / ℃、-13.5×10 -7 / ℃~25×10 -7 / ℃、-12.5×10 -7 / ℃~25×10 -7 / ℃、-11.5×10 -7 / ℃~25×10 -7 / ℃、-10.5×10 -7 / ℃~25×10 -7 / ℃、-10×10 -7 / ℃~24.5×10 -7 / ℃、-10×10 -7 / ℃~23.5×10 -7 / ℃、-10×10 -7 / ℃~22.5×10 -7 / ℃、-10×10 -7 / ℃~21.5×10 -7 / ℃、-10×10 -7 / ℃~20.5×10 -7 / ℃、-9.5×10 -7 / ℃~20×10 -7 / ℃、-9×10 -7 / ℃~19.5×10 -7 / ℃、-8.5×10 -7 / ℃~19×10 -7 / ℃、-8×10 -7 / ℃~18.5×10 -7 / ℃、-7.5×10 -7 / ℃~18×10 -7 / ℃、-7×10 -7 / ℃~17.5×10 -7 / ℃、-6.5×10 -7 / ℃~17×10 -7 / ℃、-6×10 -7 / ℃~17×10 -7 / ℃、-6×10 -7 / ℃~16.5×10 -7 / ℃、-6×10 -7 / ℃~16×10 -7 / ℃、-5.5×10 -7 / ℃~16×10 -7 / ℃、-5×10 -7 / ℃~16×10 -7 / ℃, -5×10 -7 / ℃~15.5×10 -7 / ℃, especially -5×10 -7 / ℃~15×10 -7 / ° C. If the thermal expansion coefficient within the range of 20 to 380° C. is too low or too high, the dimensional change of the processed substrate tends to become large.
[0080] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention has a thermal expansion coefficient of -20×10 -7 / ℃~30×10 -7 / ℃, -19×10 -7 / ℃~30×10 -7 / ℃, -18×10 -7 / ℃~30×10 -7 / ℃, -17×10 -7 / ℃~30×10 -7 / ℃, -16×10 -7 / ℃~30×10 -7 / ℃, -15×10 -7 / ℃~30×10 -7 / ℃, -15×10 -7 / ℃~28×10 -7 / ℃, -15×10 -7 / ℃~26×10 -7 / ℃, -14.5×10 -7 / ℃~25×10 -7 / ℃, -13.5×10 -7 / ℃~25×10 -7 / ℃, -12.5×10 -7 / ℃~25×10 -7 / ℃, -11.5×10 -7 / ℃~25×10 -7 / ℃, -10.5×10 -7 / ℃~25×10 -7 / ℃, -10×10 -7 / ℃~24.5×10 -7 / ℃, -10×10 -7 / ℃~23.5×10 -7 / ℃, -10×10 -7 / ℃~22.5×10 -7 / ℃, -10×10 -7 / ℃~21.5×10 -7 / ℃, -10×10 -7 / ℃~20.5×10 -7 / ℃, -9.5×10 -7 / ℃~20×10 -7 / ℃, -9×10 -7 / ℃~19.5×10 -7 / ℃, -8.5×10 -7 / ℃~19×10 -7 / ℃, -8×10 -7 / ℃~18.5×10 -7 / ℃, -7.5×10 -7 / ℃~18×10 -7 / ℃, -7×10 -7 / ℃~17.5×10 -7 / ℃, -6.5×10 -7 / ℃~17×10 -7 / ℃, -6×10 -7 / ℃~17×10 -7 / ℃, -6×10 -7 / ℃~16.5×10 -7 / ℃, -6×10 -7 / ℃~16×10 -7 / ℃, -5.5×10 -7 / ℃~16×10 -7 / ℃, -5×10 -7 / ℃~16×10 -7 / ℃, -5×10 -7 / ℃~15.5×10 -7 / ℃, especially -5×10 -7 / ℃~15×10 -7 / ° C. If the thermal expansion coefficient within the range of 20 to 750° C. is too low or too high, the dimensional change of the processed substrate tends to become large.
[0081] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a Young's modulus of 60 to 120 GPa, 70 to 110 GPa, 75 to 110 GPa, 75 to 105 GPa, or 80 to 105 GPa, particularly preferably 80 to 100 GPa. If the Young's modulus is too low or too high, the crystallized glass becomes easily broken.
[0082] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a modulus of rigidity of 25 to 50 GPa, 27 to 48 GPa, or 29 to 46 GPa, particularly preferably 30 to 45 GPa. If the modulus of rigidity is too low or too high, the crystallized glass becomes easily broken.
[0083] The Li2O-Al2O3-SiO2-based crystallized glass of the present invention preferably has a Poisson's ratio of 0.35 or less, 0.32 or less, 0.3 or less, 0.28 or less, 0.26 or less, and particularly preferably 0.25 or less. If the Poisson's ratio is too large, the crystallized glass becomes easily broken.
[0084] Next, a method for producing the Li2O-Al2O3-SiO2 system crystallized glass of the present invention will be described.
[0085] First, a raw material batch prepared to obtain glass of the above composition is put into a glass melting furnace, melted at 1500 to 1750°C, and then molded. The glass may be melted by a flame melting method using a burner or an electric melting method using electric heating. Melting by laser irradiation or plasma is also possible. The sample shape may be a plate, fiber, film, powder, sphere, hollow, or the like, and is not particularly limited.
[0086] Next, the obtained crystallizable glass (crystallizable glass) is heat-treated to crystallize. Specifically, the heat treatment is performed at 700 to 950°C (preferably 750 to 900°C) for 0.1 to 100 hours (preferably 1 to 60 hours) to form nuclei, followed by heat treatment at 800 to 1050°C (preferably 800 to 1000°C) for 0.1 to 50 hours (preferably 0.2 to 10 hours), and then heat treatment is performed at 900 to 1200°C (preferably 950 to 1100°C) for 0.1 to 50 hours (preferably 0.1 to 10 hours) to grow crystals. In this way, a colorless Li2O-Al2O3-SiO2-based crystallized glass in which β-spodumene solid solution crystals are precipitated as the main crystals can be obtained.
[0087] Crystallization may also be promoted by applying or irradiating sound waves or electromagnetic waves. Furthermore, the cooling rate of the crystallized glass at a high temperature may be performed at a certain temperature gradient, or may be performed at two or more levels of temperature gradient. If sufficient thermal shock resistance is desired, it is desirable to control the cooling rate to sufficiently relax the structure of the remaining glass phase. The average cooling rate from 800°C to 25°C is preferably 3000°C / min, 1000°C / min or less, 500°C / min or less, 400°C / min or less, 300°C / min or less, 200°C / min or less, 100°C / min or less, 50°C / min or less, 25°C / min or less, 10°C / min or less, and particularly 5°C / min or less in the inner part of the thickness farthest from the surface of the crystallized glass. In addition, when dimensional stability over a long period of time is desired, the cooling rate is preferably 2.5°C / min or less, 1°C / min or less, 0.5°C / min or less, 0.1°C / min or less, 0.05°C / min or less, 0.01°C / min or less, 0.005°C / min or less, 0.001°C / min or less, 0.0005°C / min or less, and particularly preferably 0.0001°C / min or less. Except for the case of physical strengthening treatment by air cooling, water cooling, etc., it is desirable that the cooling rate of the crystallized glass is close to the cooling rate from the surface to the part of the inner thickness farthest from the surface. The value obtained by dividing the cooling rate of the part of the inner thickness farthest from the surface by the cooling rate of the surface is preferably 0.0001 to 1, 0.001 to 1, 0.01 to 1, 0.1 to 1, 0.5 to 1, 0.8 to 1, 0.9 to 1, and particularly preferably 1. By being close to 1, residual strain is unlikely to occur at all positions of the crystallized glass sample, and long-term dimensional stability is easily obtained. The cooling rate of the surface can be estimated using a contact thermometer or a radiation thermometer, and the internal temperature can be estimated by placing the high-temperature crystallized glass in a cooling medium and measuring the heat quantity and rate of heat change of the cooling medium, and then using this numerical data and the specific heat and thermal conductivity of the crystallized glass and the cooling medium.
[0088] The Li2O-Al2O3-SiO2 crystallized glass of the present invention may be subjected to chemical strengthening or the like. The conditions of the chemical strengthening treatment may be appropriately selected by considering the glass composition, the degree of crystallization, the type of molten salt, and the like, and the treatment time and temperature. For example, a glass composition containing a large amount of Na2O that may be contained in the remaining glass may be selected so that chemical strengthening after crystallization is easy, or the degree of crystallization may be intentionally reduced. The molten salt may contain an alkali metal such as Li, Na, or K alone or in combination. Furthermore, not only the usual one-stage strengthening but also multi-stage chemical strengthening may be selected. In addition, the Li2O-Al2O3-SiO2 crystallized glass of the present invention may be treated by chemical strengthening or the like before crystallization, so that the Li2O content on the sample surface can be reduced more than that inside the sample. When such glass is crystallized, the crystallization degree of the sample surface becomes lower than that inside the sample, the thermal expansion coefficient of the sample surface becomes relatively high, and compressive stress due to the thermal expansion difference can be applied to the sample surface. Furthermore, when the crystallinity of the sample surface is low, the glass phase increases on the surface, and the chemical resistance and gas barrier properties can be improved by selecting the glass composition. EXAMPLES
[0089] The present invention will be described below based on examples, but the present invention is not limited to the following examples. Tables 1 to 4 show examples of the present invention (samples Nos. 1 to 5 and 7 to 25) and a comparative example (sample No. 6).
[0090] [Table 1]
[0091] [Table 2]
[0092] [Table 3]
[0093] [Table 4]
[0094] First, each raw material was mixed in the form of oxide, hydroxide, carbonate, nitrate, etc., so as to obtain glass having the composition shown in Tables 1 to 4, and a glass batch was obtained. The obtained glass batch was placed in a crucible containing platinum and rhodium, a reinforced platinum crucible not containing rhodium, a refractory crucible, or a quartz crucible, and melted at 1600°C for 4 to 100 hours, then heated to 1650 to 1680°C and melted for 0.5 to 20 hours, rolled to a thickness of 5 mm, and further heat-treated at 700°C for 30 minutes using an annealing furnace, and the annealing furnace was cooled to room temperature at 100°C / h to obtain a crystallizable glass. The melting was performed by an electric melting method that is widely used in the development of glass materials.
[0095] It was confirmed that the glass composition of sample No. 15 could be melted by burner heating, electric heating, laser irradiation, etc., and that the glass sample could be formed into a hemispherical, spherical, fiber, powder, thin plate, tube, or bulb shape by pressing, redrawing, spraying, rolling, filming, overflow (fusion), hand-blowing, etc. Furthermore, it was confirmed that the glass composition of sample No. 16 could be used to pour a molten glass onto a liquid with a higher specific gravity than sample No. 16, and then solidified into a plate shape by cooling. Incidentally, the glasses produced by any of the methods were successfully crystallized under the conditions shown in the table.
[0096] The Pt and Rh content of the prepared samples was analyzed using an ICP-MS device (Agilent8800, manufactured by AGILEINTTECHNOLOGY). First, the prepared glass samples were crushed and wetted with pure water, and then perchloric acid, nitric acid, sulfuric acid, hydrofluoric acid, etc. were added to melt them. The Pt and Rh content of the samples was then measured using an ICP-MS. The Pt and Rh content of each measurement sample was determined based on a calibration curve prepared using a previously prepared Pt and Rh solution with known concentrations. The measurement mode was Pt:He gas / HMI (low mode) and Rh:HEHe gas / HMI (medium mode), and the mass numbers were Pt:198 and Rh:103. The Li2O content of the prepared samples was analyzed using an atomic absorption spectrometer (ContrAA600, manufactured by Analytik Jena). The flow of melting the glass samples and the use of the calibration curves were basically the same as for the Pt and Rh analysis. As for other components, they were measured by ICP-MS or atomic absorption spectrometry in the same way as Pt, Rh, and Li2O, or glass samples with known concentrations previously examined using an ICP-MS or atomic absorption spectrometry were used as calibration curve samples, and calibration curves were then created using an XRF analyzer (RIGAKU ZSX PrimusIV) and the actual content of each component was determined from the XRF analysis values of the measurement sample based on the calibration curve. During XRF analysis, the tube voltage, tube current, exposure time, etc. were adjusted as necessary depending on the components being analyzed.
[0097] The prepared glass was subjected to nucleation under the heat treatment conditions shown in the table, followed by crystal growth and crystallization. The obtained crystallized glass was evaluated for transmittance, precipitated crystals, thermal expansion coefficient, Young's modulus, rigidity modulus, Poisson's ratio, cracking, and color.
[0098] The transmittance was evaluated by measuring the transmittance at each wavelength using a spectrophotometer for a crystallized glass plate with a thickness of 2 mm and optically polished on both sides. A spectrophotometer V-670 manufactured by JASCO was used for the measurement. An integrating sphere unit "ISN-723" was attached to the V-670. The measurement wavelength range was 200-1500 nm, the scan speed was 200 nm / min, the sampling pitch was 1 nm, and the bandwidth was 5 nm in the wavelength range of 200-800 nm and 20 nm in other wavelength ranges. Before the measurement, baseline correction (100% adjustment) and dark measurement (0% adjustment) were performed. The dark measurement was performed with the barium sulfate plate attached to the ISN-723 removed.
[0099] The precipitated crystals were evaluated using an X-ray diffractometer (Rigaku's fully automated multipurpose horizontal X-ray diffractometer Smart Lab). The scan mode was 2θ / θ measurement, the scan type was continuous scan, the scattering and divergence slit width was 1°, the receiving slit width was 0.2°, the measurement range was 10-60°, the measurement step was 0.1°, and the scan speed was 5° / min. The precipitated crystal species identified at this time was β-spodumene solid solution, which is shown in the table as "β-S".
[0100] The thermal expansion coefficient was evaluated by measuring the average linear thermal expansion coefficient of a crystallized glass sample processed to 20 mm × 3.8 mmφ in temperature ranges of 20 to 200° C., 20 to 380° C., and 20 to 750° C. A NETZSCH Dilatometer was used for the measurement.
[0101] The Young's modulus, rigidity modulus, and Poisson's ratio were measured at room temperature using a free resonance type elastic modulus measuring device (JE-RT3, manufactured by Nippon Technoplus) for plate samples (40 mm x 20 mm x 2 mm) whose surfaces had been polished with a polishing solution containing dispersed No. 1200 alumina powder.
[0102] Regarding cracks, the crystallized glass in which no cracks were visually observed was rated as "◯", and the crystallized glass in which cracks were visually observed was rated as "×".
[0103] The color of the crystallized glass was evaluated by visual inspection as "◯" if it was colorless, and "×" if it was not colorless.
[0104] As is clear from Tables 1 to 4, the crystallized glass of samples No. 1 to 5 and 7 to 25 had β-spodumene solid solution precipitated as the main crystal, had high transmittance in the ultraviolet to infrared range, and had a low thermal expansion coefficient. In addition, no cracks were observed and they were colorless. The crystallized glass of No. 6, which is a comparative example, had a yellow appearance and low transmittance in the ultraviolet range.
[0105] As is clear from Table 2, the Li2O-Al2O3-SiO2 crystallized glass of the present invention can be crystallized in a short time and can obtain high transmittance. Although the crystallization conditions can be changed depending on the required characteristics, the crystallization can be performed at a process speed comparable to that of the conventional Li2O-Al2O3-SiO2 crystallized glass, so that the existing equipment can be used and the glass can be manufactured at low cost. [Industrial Applicability]
[0106] The Li2O-Al2O3-SiO2 crystallized glass of the present invention has high transmittance in the ultraviolet to infrared range and low thermal expansion, so it is particularly suitable for semiconductor substrates.It is also suitable for front windows of oil stoves, wood stoves, etc., substrates for high-tech products such as color filters and image sensor substrates, setters for firing electronic components, light diffusion plates, furnace tubes for semiconductor manufacturing, masks for semiconductor manufacturing, optical lenses, members for dimensional measurement, members for communication, members for construction, containers for chemical reactions, top plates for electromagnetic cooking, heat-resistant tableware, heat-resistant covers, window glass for fire doors, members for astronomical telescopes, members for space optics, etc.
Claims
【Request 1】 In mass%, SiO 2 40-90%, Li 2 O 1 to 10%, Al 2 O 3 16-30%, SnO 2 0-20%, ZrO 2 More than 0 to 20%, SnO 2 + ZrO 2 3.3-30%, TiO 2 0-2% or less, MgO 0-10%, P 2 O 5 0 to 10%, ZnO 0 to 2%, and the mass ratio is MgO / (Li 2 O + MgO) is 0.0005 or more, (Li 2 O+Na 2 O+K 2 O) / ZrO 2 Li alloys characterized in that the content of F is 0.1 to 6% and As 2 O 3 is 0.05 to 8% and β-spodumene solid solution is precipitated as the main crystal. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 2】 Furthermore, in mass%, Na 2 O 0-10%, K 2 O 0-10%, CaO 0-10%, SrO 0-10%, BaO 0-10%, ZnO 0-2%, B 2 O 3 The Li according to claim 1, characterized in that it contains 0 to 10% 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 3】 In mass%, SnO 2 3. The Li according to claim 1, wherein the Li content is 0 to 2%. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 4】 In mass%, ZrO 2 The Li according to any one of claims 1 to 3, characterized in that it contains 1.5 to 20% and MgO 0 to 10%. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 5】 Further, in mass%, Fe 2 O 3 The Li according to any one of claims 1 to 4, characterized in that it contains 0.10% or less. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. [Request 6] In terms of mass ratio, Al 2 O 3 / (SnO 2 + ZrO 2 6. The Li according to any one of claims 1 to 5, wherein 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 7】 In terms of mass ratio, SnO 2 / (SnO 2 + ZrO 2 + TiO 2 +P 2 O 5 +B 2 O 3 ) is 0.01 or more, 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 8】 In terms of mass ratio, ZrO 2 / Li 2 The Li according to any one of claims 1 to 7, characterized in that O is 0.4 or more. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 9】 In terms of mass ratio, (SnO 2 + ZrO 2 + TiO 2 ) / (SiO 2 +Al 2 O 3 + Li 2 O+Na 2 O+K 2 O+MgO+CaO+SrO+BaO+ZnO+B 2 O 3 +P 2 O 5 ) is 0.03 or more, 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 10】 In terms of mass ratio, (SiO 2 +Al 2 O 3 ) / Li 2 Li according to any one of claims 1 to 9, characterized in that O is 20 or more. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics.
11. In terms of mass ratio, TiO 2 / ZrO 2 The Li according to any one of claims 1 to 10, wherein 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 12】 In terms of mass ratio, TiO 2 / (TiO 2 +Fe 2 O 3 ) is 0.001 to 0.999, 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. [Request 13] In mass%, HfO 2 +Ta 2 O 5 Li according to any one of claims 1 to 12, characterized in that it contains less than 0.05% 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. [Request 14] The Li according to any one of claims 1 to 13, characterized in that it contains Pt 7 ppm or less by mass%. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 15】 The Li according to any one of claims 1 to 14, characterized in that it contains Rh 7 ppm or less in mass %. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics.
16. The Li according to any one of claims 1 to 15, characterized in that it contains 9 ppm or less of Pt + Rh in mass %. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 17】 The thermal expansion coefficient at 20 to 200°C is -20×10 -7 / ℃~30×10 -7 / °C. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. [Request 18] The thermal expansion coefficient at 20 to 380°C is -20×10 -7 / ℃~30×10 -7 / °C. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics.
19. The thermal expansion coefficient at 20 to 750°C is -20×10 -7 / ℃~30×10 -7 / °C according to any one of claims 1 to 18. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 20】 The Li-based composition according to any one of claims 1 to 19, characterized in that the Li-based composition has a colorless appearance. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics.
21. The Li-based film according to any one of claims 1 to 20, having a thickness of 2 mm and a transmittance of 1% or more at a wavelength of 360 nm. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 22】 The Li-based film according to any one of claims 1 to 21, having a thickness of 2 mm and a transmittance of 10% or more at a wavelength of 555 nm. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. [Request 23] The Li-based film according to any one of claims 1 to 22, having a thickness of 2 mm and a transmittance of 35% or more at a wavelength of 1070 nm. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics. 【Request 24】 Thickness: 2 mm; transmittance at a wavelength of 360 nm: 1% or more; thermal expansion coefficient at 20 to 200°C: -20×10 -7 / ℃~30×10 -7 / ° C., and β-spodumene solid solution is precipitated as the main crystal. 2 O-Al 2 O 3 -SiO 2 Glass-ceramics.
Citation Information
Patent Citations
Crystalline glass having high strength and low expansion
JP1983049634A
Heat resistance transparent crystallized glass
JP1991023237A
Glass composition for magnetic disk substrate and magnetic disk substrate
JP1998226532A
Li2-al2o3-sio2 based glass ceramics
JP1999228181A
Lithium oxide-alumina-silicon dioxide crystallized glass and method for producing the same
JP2005053711A